Inheritance of aposporous apomixis in interspecific hybrids derived from sexual paspalum plicatulum and apomictic paspalum guenoarum - Aguilera, Patricia Mabel; Galdeano, Florencia; Quarin, Camilo Luis; Ortíz, Juan Pablo Amelio; Espinoza, Francisco (Crop Science Society of America, 2015)
Apomictic Paspalum plicatulum Michx. and P.guenoarum Arechav. are promising candidates for forage grass development in tropical regions. From a plant breeding perspective, apomixis provides a unique mechanism for developing superior cultivars and preserving them indefinitely. Therefore, analysis of its inheritance is of great interest in these apomictic species. The objective of this work was to analyze the inheritance and expressivity of apomixis in interspecific families derived from crosses between a sexual colchicine-induced plant of P. plicatulum and an apomictic P. guenoarum plant. One F1, one F2, and three backcross (BC) populations were created. Amplified fragment-length polymorphism (AFLP) markers confirmed the hybrid origin of the F1 descendants. Analysis of the reproductive mode of the F1 by flow cytometry seed screen (FCSS) showed a segregation ratio of 1.6:1 sexual vs. apomictic plants. The same analysis in F2 and BC populations showed that in selfing or crosses involving sexual genotypes all progeny reproduced by sexuality, while BC populations involving apomictic hybrids as pollen donors produced offspring that segregated for the reproductive mode. Apomixis can be transmitted by pollen from P. guenoarum to other species of the Plicatula group as a simplex (Aaaa) Mendelian dominant factor, and full sexual reproduction requires the homozygous recessive (nulliplex) condition (aaaa) for the apomixis determinant. Results provided here are of interest for breeding apomictic species of Plicatula and for basic research on the genetic determinants of apomixis. Also, the possibility of creating new apomictic cultivars by traditional breeding methods is presented.
Keywords: Aposporous apomixis; Sexual saspalum plicatulum; Apomictic paspalum guenoarum; Forage grass